Comparison of the effect of High Intensity Interval Training and Low Intensity Interval Training (HIIT) Functional Training Methods on Body Fat Percentages - Hariadi Hariadi; Ardi Nusri; Fery Juanda (Journal Physical Education, Health and Recreation, 2019)
Functional training is one of the most widely used training methods to reduce obesity. There are various types of functional training methods, for this reason, an analysis is needed to compare the effect of these methods through a measurement. This study aims to compare the popular functional training methods High Intensity Interval Training (HIIT) and Low Intensity Steady State (LISS) to body fat percentages. Measurements were taken on 20 women assisted by InBody 270. This study used purposive sampling and used a matching by pairing technique. Data was analysed using t-test. The result shows that the first hypothesis is 4.398> 2.101, which means that there was a significant effect of the HIIT functional training method on percent body fat. In the second hypothesis 13.365> 2.101, which means that there was a significant effect of the LISS functional training method on percent body fat. In the third hypothesis 8.966> 2.028, which means that there was a significant effect of the functional training method HIIT and the functional training method LISS on percent body fat. Based on the mean difference (mean df), the decrease in percent body fat in the functional training group HIIT method is higher (2.47) than LISS method of 1.42. It can be concluded that the functional training method of HIIT is more effective in reducing body fat percentages.